(untitled) (Journal of the College of Education for Women, 2019)
Allah’s wisdom has necessitated concentrating un human nature the ability ofmediation and forethought .among the aspect of this ability is the recognition of therelationship between causes and effects issues and reasons behind them and thesensing of similarities and differences and distinguish the connection between thesubjects and characteristics and the innate perception of material and immaterial goodand bad.Allah’s wisdom has willed not to make his law away from the nature of people ofdiscovering the relationship between things and their causes, or similarity betweenthings and their counterparts to use the Quranic text to convince reason and to enablereason to realize the wisdom quranic text within the limits of Islamic law.Hence, it is necessary to mediate upon causes of Islamic rulings .the causemight be what we took from the legislator(Allah) or it might be precepted through informed reasoning. Some causes might bekept hidden by the legislator (Allah) to achieve servitude and complete obedience toAllah without degrading the role of reason, and to make servitude to Allah as absoluteas possible in order to make to rewarding and punishment.The cause in some texts is intransitive that’s why some fundamentalistsattempt to interpret by the results and intention of actions and the resulting benefitsand corruption; and that’s what is called "wisdom".Its worth mentioning that my professor ,Dr .Mohammed Fadhil As-samaraiwas the one who referred to this subject when studying analogy at the stage ofD.courses, I was driven into a "A Fundamental Study of Nissa Sura",but was quiteoccupied by this subject that’s why I have chosen it as my first research.The conclusion of the present study has shown the following:1-There is a difference between wisdom and cause. While the wisdom is the source ofthe legislation of the ruling, the cause is the controlled explicit issue of the knownruling on which the ruling is based.2-The saying of prohibition of cause by wisdom is not reasonable to make cause isgeneral and it may be expanded. The preference issue is to be in between.3- This study has a peculiar benefit. It shows a specific knowledge of the reasonswhich fall behind the differences occurs between jurists rarely mentioned in othercontemporary studies. The other benefits of this study is to give the ruling for newthings which need explanation derived from Islamic jurisprudence and into completecanonical laws of Islam.